2011
DOI: 10.1152/japplphysiol.00157.2011
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive and bioactive growth hormone responses to resistance exercise in men who are lean or obese

Abstract: The present study was designed to examine the effects of a highvolume, whole body acute resistance exercise (RE) protocol on immunoreactive GH (iGH), bioactive GH (bGH), and GH-binding protein (GHBP) in sedentary lean and obese men. Nine obese (mean Ϯ SD: 20.8 Ϯ 2.1 yr old, 177.0 Ϯ 4.1 cm height, 108.7 Ϯ 15.9 kg body mass, 37.6 Ϯ 5.29% body fat) and nine lean (20.1 Ϯ 2.1 yr old, 177.8 Ϯ 8.7 cm height, 71.7 Ϯ 5.8 kg body mass, 14.7 Ϯ 3.54% body fat) men completed an acute RE protocol (6 exercises, 3 sets of 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…However, the overall GH response evaluated through the AUC analyses showed a dampened GH response; which is in agreement with previous studies (Ormsbee et al 2009;Thomas et al 2011). Excessive body fat and/or high insulin levels in obese could have contributed to the lower baseline GH concentration in this group by disrupting the GH signaling pathway (Ji et al 1999;Succurro et al 2009).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the overall GH response evaluated through the AUC analyses showed a dampened GH response; which is in agreement with previous studies (Ormsbee et al 2009;Thomas et al 2011). Excessive body fat and/or high insulin levels in obese could have contributed to the lower baseline GH concentration in this group by disrupting the GH signaling pathway (Ji et al 1999;Succurro et al 2009).…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies evaluating GH response to RE, a lower GH response was observed in obese compared to lean sedentary men (Ormsbee et al 2009;Thomas et al 2011). However, these referenced studies did not include IGF-1.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Specifically, lower GH concentrations in men immediately after exercise might have resulted in a relatively higher growth hormone receptor (GHR) presence. Since growth hormone binding protein (GHBP) is thought to be produced from the proteolytic cleavage of GHRs [3,42], it is conceivable that an increase in GHRs could in turn increase GHBP concentrations, resulting in an extended biological half-life of GHBPbound GH [43]. This could then extend the biological half-life compared to free GH, resulting in the observation of a sustained GH increased at +30.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no change was observed in IGF-1, despite a higher GH during 12 weeks of resistance-exercise training in the HP group. Previous studies of the acute or chronic effect of exercise on circulating IGF-I have produced inconsistent results, with levels being reported to decline, to increase, or to remain unchanged after the onset of exercise 33,34 . Finally, data from the present study appear to support the importance of a fine balance between anabolism and catabolism during chronic moderate-high intensity resistance training with proper diet.…”
Section: Discussionmentioning
confidence: 99%